Diagnosis of skeletal muscle channelopathies. (November 2013) - Spillane, Jennifer; Fialho, Doreen; Hanna, Michael G
Abstract : Introduction: Skeletal muscle channelopathies are rare disorders of muscle membrane excitability. Their episodic nature may result in diagnostic difficulty and delays in diagnosis. Advances in diagnostic clinical electrophysiology combined with DNA-based diagnosis have improved diagnostic accuracy and efficiency. Ascribing pathogenic status to identified genetic variants in muscle channel genes may be complex and functional analysis, including molecular expression, may help with this. Accurate clinical and genetic diagnosis enables genetic counselling, advice regarding prognosis and aids treatment selection. Areas covered: An approach to accurate and efficient diagnosis is outlined. The importance of detailed clinical evaluation including careful history, examination and family history is emphasised. The role of specialised electrodiagnostics combined with DNA testing and molecular expression is considered. New potential biomarkers including muscle MRI using MRC Centre protocols are discussed. Expert opinion: A combined diagnostic approach using careful clinical assessment, specialised neurophysiology and DNA testing will now achieve a clear diagnosis in most patients with muscle channelopathies. An accurate diagnosis enables genetic counselling and provides information regarding prognosis and treatment selection. Genetic analysis often identifies new variants of uncertain significance. In this situation, functional expression studies as part of a diagnostic service will enable determination of pathogenic status of novel genetic variants.